ANALYSIS OF NEED FOR DEVELOPING A POETRY READING TRAINING MODEL THROUGH REFLECTIVE SPEAKING - Atqia, Wirani; Muliastuti, Liliana; Rafli, Zainal (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to analysis the need for developing a poetry reading training model that integrates a reflective speaking approach as a means of improving the skills of expression, intonation, interpretation, and understanding the meaning of poetry. The reflective speaking approach is a speaking activity that requires the interpretation and reflection of the content and meaning contained in the poem. The method used in this study is qualitative descriptive research with data collection techniques in the form of in-depth interviews, questionnaires, and observations. The subjects of the study consisted of Indonesian language teachers, poetry reading trainers, artists, and students at the adolescent to college level. The results of the analysis showed that participants had difficulty in understanding the meaning of poetry in depth and channel it in the form of expressive reading. These findings indicate the need to develop a poetry reading training model based on a reflective process, with training strategies that involve discussions of meaning, reflective speaking exercises, tone enrichment exercises, and interpretive reading. This model is expected to improve poetry reading skills while forming an appreciative and empathetic character in training participants.